Effect on silicon nitride thin films properties at various powers of RF magnetron sputtering - Mustafa, Mohd Kamarulzaki; Majeed, Uzair; Iqbal, Younas (Science Publishing Corporation, 2018)
Silicon nitride thin films have numerous applications in microelectronics and optoelectronics fields due to their unique properties. In this work, silicon nitride thin films were produced using radio frequency (R.F.) magnetron sputtering technique at various sputtering powers. The prepared thin films were characterized with XRD, FE-SEM, FTIR, surface profiler, AFM and spectral reflectance techniques for structure, surface morphology, chemical bonding information, growth rate, surface roughness and optical properties. The results showed that silicon nitride thin films were amorphous in nature. The films were smooth and densely packed with no voids or cracks at the surface. FTIR characterization informed about Si-N bonding existence which confirmed the formation of silicon nitride films. The sputtering power showed the impetus effect on growth rate, surface roughness and optical properties of produced films.